Comparison of Chemical Structure of Alginite Humic Acids Isolated with Two Different Procedures with Soil Humic Acids - Barančíková Gabriela; Litavec Tadeáš (Agriculture, 2016)
The different origin of alginite and soil organic matter may be the reason of differences in their humic acids (HA) chemical structure. One of the aims of this article is to compare the chemical composition of alginite HA and HA isolated from different soil types. Another aim of this article is to compare the chemical structure of humic acids of alginite isolated with two different procedures: modified IHSS (International Humic Substances Society) method and simplified extraction method. The modified IHSS method was applied for the isolation of alginite and soil HA. To obtain sufficient amount of alginate HA for biological experiments, simplified extraction method suited for large volumes of HA was applied. The differences in elemental analysis and ash proportion in HA extracted by modified IHSS method (C = 35.4, H = 43 atomic%, ash content = 0.08%) and simplified extraction method (C = 31, H = 31 atomic%, ash content = 7.42%) can be caused by different concentration of extraction solution and also differences in purification of HA. The differences in chemical structure between alginate HA and HA isolated from different soil types according to the data of elemental analysis (C content of alginite HA = 35.4 atomic%, C content in soils HA = 38.2‒49.1 atomic%) and 13C nuclear magnetic resonance (NMR) spectra (degree of aromaticity of alginite HA = 24.4% and soil HA= 35.9‒53%) were found. Results of 13C NMR show that the content of aromatic carbon was decreasing in the following order: Haplic Chernozem HA > Andic Cambisol HA > Haplic Cambisol HA > alginite HA. Based on the obtained results, it can be concluded that the differences in the chemical structure of alginite and soil HA can be explained by the difference in the origin of organic matter in alginite and soil samples. The source of organic matter in alginite is mainly type II kerogen from algae and that of soil is lignin and cellulose (type III kerogen) of higher plants.